Analisis Kinerja Keuangan Pemerintah Daerah Setelah Penerapan Standar Akuntansi Pemerintahan Berbasis Akrual - Budhi Purwantoro Jati; Takrisia Umara Pangestu (Akademi Akuntansi YKPN Yogyakarta, 2021)
This study aims to analyze and find out how the financial perfomance of the local government of Sleman Regency after implementation of Accrual-Based Govermental Accounting Standard from 2015 until 2019. The regional financial performance seen from financial independence ratio, dependency ratio, decentralization degree ratio, PAD effectiveness ratio, financial efficiency ratio, revenue growth ratio, spending efficiency ratio, and spending compatibility ratio. The result of this study indicate that the financial performance of the Sleman Regency Government is generaly said to be quite good. In terms of performance of the implementation of the revenue budget, the effectiveness of PAD ratio can be considered very effective because the average effectiveness by 110,67%. The regional financial efficiency ratio is also efficient with an average ratio of 89,18%, and the regional revenue growth ratio show a positive with an average growth rate of 6,54%. In terms of regional spending budget realization performance, the spending efficiency ratio is classified as efficient with an average ratio of 87,37%. The portion of regional spending allocated for operating expenditure is larger than capital expenditure, which are 82,25% and 17,73%, respectively. This allocation is quite reasonable, considering that Sleman Regency Government is the district with largest APBD realization among other regencies/cities in the Special Region of Yogyakarta. However, the regional financial independence of the Sleman Regency Government is still relatively low with an average ratio of 47,64% and the pattern of its relationship with the central government is included in the consultative category. This is in line with the level of dependence on central government which is still very high with an average ratio of 66,51%. The ratio of decentralization is considered quite because the average degree of decentralization by 31,51%. The trend regional financial independence and the degree of decentralization, shows a positive direction of development, and conversely the level of dependence tends to decrease